Voltage Deviation in Breaker-testing Station Study Using ADPSS - Zhenan Zhang; Hua Wang; Qionglin Li; Xiaomeng Li (Institute of Advanced Engineering and Science, 2014)
With the fast development of China power grid, more and more power system devices such as breakers are applied. Breaker testing also becomes very important. At the same time the testing procedure will cause voltage deviation around the breaker-testing station. Big voltage deviation can make severe damage for the power customers. Based on the power system simulation software ADPSS developed by China Electric Power Research Institute (CEPRI), this paper built up the simulation model using the electromechanical-electromagnetic transient hybrid method, and simulated the voltage deviation in a Henan breaker-testing station. The simulation results showed that with the higher testing breaker current level, bigger voltage deviation is caused. Finally this paper suggested a testing breaker current level for the breaker-testing station with Power Quality Criteria. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5101